Guest

tan^2(180/16)+tan^2(360/16)+tan^2(540/16)+........+tan^2(1260/16)=

tan^2(180/16)+tan^2(360/16)+tan^2(540/16)+........+tan^2(1260/16)=

Grade:Select Grade

1 Answers

Arun
25758 Points
5 years ago
we will use formula tan^2a=(1-cos2a)/(1+cos2a)
= tan^(pi/16)+tan^2(7pi/16)+tan^(2pi/16)+tan^2(6pi/16)+tan^2(3pi/16)+tan^2(5pi/16)+tan^(4pi/16)
= tan^(pi/16)+tan^2(pi/2-pi/16)+tan^2(2pi/16)+tan^2(pi/2-2pi/16)+tan^2(3pi/16)+tan^2(pi/2-3pi/16)+tan^2(pi/4)
= tan^2(pi/16)+cot^2(pi/16)+tan^2(2pi/16)+cot^2(2pi/16)+tan^2(3pi/16)+cot^2(3pi/16)+1
we use formula
tan^2a+cot^2a=(1-cos2a)/(1+cos2a)+(1+cos2a)/(1-cos2a)
=2(1+cos^2(2a))/sin^2(2a))
hence
= 2(1+cos^2(pi/8))/sin^2(pi/8) +2(1+cos^2(pi/4))/sin^2(pi/4) +2(1+cos^2(3pi/8))/sin^2(3pi/8) +1
= 2(cosec^2(pi/8)+cot^2(pi/8)+cosec^2(3pi/8)+cot^2(3pi/8)+2(1+1/2)/(1/2) +1
= 2(1+2cot^2(pi/8)+1+2cot^2(3pi/8))+6+1
= 4+6+1+4(cot^2(pi/8)+cot^2(3pi/8))
= 11+4{(1+cospi/4)/(1-cos(pi/4)) + (1+cos(3pi/4))/(1-cos(3pi/4)}
= 11+4{(1+1/sqrt2)/(1-1/sqrt2) +(1-1/sqrt2)/(1+1/sqrt2)}
= 11+4{2*3/2)/(1/2)
= 11+4(6)
= 11+24
= 35  (Answer)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free